Semi-automatic generation of shear wall structural models. (May 2023) - Zhou, Xuhong; Huang, Xuesi; Liu, Jiepeng; Cheng, Guozhong; Wang, Lufeng; Hu, Jiahao; Liu, Pengkun; Chen, Y.Frank
Abstract: Manual creation and adjustment of a structural model is time-consuming and could be erroneous. Thus, a semi-automatic generation method based on little manual operation for shear wall structural models is proposed. It includes fast room identification based on graph structure and depth-first search, a complete process of generating structural members including shear walls, structural beams, and slabs, and a rapid process of load modeling. The method is proven accurate and effective in member and load modeling, as demonstrated by two actual engineering cases. Specifically, the structural model is adequately controlled by parameters; the members are correctly generated and interconnected; the load magnitude and arrangement are consistent with the manual results; and the time consumption is generally within one minute. Thus, the proposed method can assist in structural modeling tasks and provide a high-speed information communication between architectural drawings and structural calculation software.